The Determinants of the Bid-Ask Spread Components - Liang, Xiuying (2006)
Reported bid-ask spread decompositions vary in exchange structure, for example quotedriven, order-driven or hybrid systems. The majority however, focus on quote-driven markets. This dissertation empirically studies the decomposition of spread components in a order-driven market and identifies relations among the individual components and firm-specific attributes such as trading volume, trade size, share price, volatility of returns, information arrival and market capitalisation. The data used are from a sample of FTSE 100 stocks since the 1997 movement from a quote-driven system to the order-driven system. Based on the sample observations, I implement two decomposition methodologies to estimate the order processing, asymmetric information and inventory holding costs. Each component is then regressed on the six characteristics variables to examine their relationship.